AIDS in a three-year old girl - Dyah Kanya Wati; Bagus Ngurah Putu Arhana; Dewi Kumara Wati; Tuti Parwati Merati (Paediatrica Indonesiana, 2006)
The acquired immunodeficiency syndromein children was first recognized in 1982, oneyear after the initial description in adults.WHO estimates that 2 million children hadbeen infected with human immunodeficiency virus(HIV) by the year 2000. Pediatric AIDS threatenschild survival in developing countries. At the endof 1999, 34.3 million individuals were estimated tobe infected globally, of which 1.3 million (3.8%)were children below 15 years old. Until September2005, no children with HIV AIDS in Indonesia wasfound.Approximately 80% of children acquired HIV-1infection from vertical maternal transmission; the restare infected from contaminated blood products,infected organs, breastfeeding, or sexual abuse.Two general patterns of congenital infection arerecognized. Twenty percent of infected infants developearly disease, while the rest progress slowly, developinginto AIDS in adolescents. The most successfulapproach in the management of children with HIVrequires a multidisciplinary team approach.